Heat dissipation coating containing modified nanoparticles and preparation method thereof
By combining modified nanoparticles with graphene and mixing them with aqueous resins and other materials, a heat dissipation coating with excellent heat dissipation performance, good adhesion and hardness is prepared, which solves the problem of nanomaterials being easily agglomerated and fall off in the coating. Maintain high thermal conductivity in moisture-absorbing environments.
Patent Information
- Application Number
- CN202411740451.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Nanomaterials are prone to agglomeration, shedding or migrating in coatings, affecting the adhesion and hardness of the coating, and the thermal conductivity will decrease in humidity or liquid environments, limiting the use range of heat dissipation coatings.
By modifying the nanoparticles with silane coupling agent and mixing them with graphene, and then heat treatment, the modified nanoparticles are obtained, and mixed with aqueous resin dispersion, defoaming agent, dispersant and leveling agent to perform ball milling Treatment to prepare a heat dissipation coating with improved adhesion and hardness.
It significantly improves the heat dissipation performance of the heat dissipation coating, enhances adhesion and hardness, and has a very small thermal conductivity loss after moisture absorption treatment, expanding the scope of use of the coating.
Smart Images

Figure BDA0005162503500000071 
Figure BDA0005162503500000101 
Figure BDA0005162503500000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a heat dissipation coating containing modified nanoparticles and a preparation method thereof. Background Art
[0002] Thermal coating is a coating that can enhance the heat dissipation performance of an object. Its main components include polymer or silicone modified acrylic resin, thermal conductive filler, additives and solvents. Thermal conductive filler is the key component to improve the heat dissipation performance of thermal coating. Common thermal conductive fillers include metal fillers, non-metallic fillers and graphene. In order to make the coating have excellent heat dissipation effect, good film forming properties and smooth construction, current research often uses nanoparticles as thermal conductive fillers. A small amount of addition to the coating can make the coating have excellent heat dissipation effect, such as nano-alumina, nano-boron nitride, nano-silicon carbide, nano-silicon nitride or nano-aluminum nitride.
[0003] However, in actual use and research, it was found that nanomaterials are prone to agglomeration in coatings due to their extremely small size and high specific surface area. The interaction between nanoparticles and the coating matrix is weak, and they are prone to falling off or migration, affecting the adhesion and hardness of the coating. In addition, the nanoparticle heat dissipation coating is thin, and once scratched or corroded, the function of the nanocoating will be affected and cannot be repaired. In actual research, it was also found that the thermal conductivity of some coatings using nanoparticles will gradually decrease in high humidity or liquid environments, such as nano-alumina and aluminum nitride. It is possible that they absorb moisture, resulting in a decrease in thermal conductivity. Even if the nanoparticles are surface treated with silane coupling agents, it cannot be guaranteed that 100% of the surface is covered, which will affect its thermal conductivity, thereby limiting the scope of use of heat dissipation coatings. Summary of the invention
[0004] The purpose of the present invention is to provide a heat dissipation coating containing modified nanoparticles and a preparation method thereof in order to solve the above problems.
[0005] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0006] A heat dissipation coating containing modified nanoparticles, wherein the raw materials for preparing the heat dissipation coating include, by weight, 40-60 parts of an aqueous resin dispersion, 15-20 parts of modified nanoparticles, 0.1-0.2 parts of a defoamer, 0.1-0.5 parts of a dispersant, and 1-2 parts of a leveling agent;
[0007] The modified nanoparticles are obtained by modifying nanoparticles with a silane coupling agent, mixing with graphene, and then heat treating the nanoparticles. The nanoparticles are one of nano-aluminum oxide, nano-boron nitride, nano-silicon nitride, or nano-aluminum nitride.
[0008] Furthermore, the solid content of the aqueous resin dispersion is 30-50wt%; the aqueous resin dispersion is one or a combination of aqueous acrylic resin, aqueous epoxy resin, aqueous polyurethane, and aqueous silicone resin.
[0009] Furthermore, the preparation of the modified nanoparticles comprises the following steps:
[0010] (1) uniformly dispersing the dried nanoparticles in 75 wt% ethanol, adding a silane coupling agent to condense and reflux, centrifuging to obtain a precipitate, washing, and vacuum drying; mixing the graphene powder with a citric acid solution, adjusting the pH to alkaline, and sealing the mixture in a container, heating the mixture to react at a constant temperature, cooling the mixture to room temperature after the reaction is completed, and taking out the reactant, washing, and drying the mixture;
[0011] (2) uniformly dispersing the treated nanoparticles and the treated graphene in a solvent, filtering the filtrate, heat-treating the filtrate, and grinding to obtain modified nanoparticles.
[0012] Furthermore, the added amount of the silane coupling agent is 2-4% of the mass of the nanoparticles.
[0013] Furthermore, the processing process of the graphene powder is specifically as follows: dissolving citric acid in deionized water to obtain a citric acid solution, then dispersing the graphene powder in the citric acid solution, adjusting the pH to 7-8 using sodium hydroxide, and then sealing the solution in a reactor, heating it to 200-240°C, keeping the temperature constant for 12-48h, taking out the reactant after cooling, washing and drying, and the mass ratio of citric acid to graphene powder is (5-10):1.
[0014] Furthermore, after the graphene powder is dispersed in the citric acid solution, triethylenediamine is added, and after mixing, the pH is adjusted to 7-8 using sodium hydroxide, and the amount of triethylenediamine added is 50% of the mass of the graphene powder.
[0015] Furthermore, in terms of mass percentage, the processed nanoparticles account for 10-30%, and the processed graphene accounts for 70-90%.
[0016] Furthermore, the solvent is N-methylpyrrolidone, polyvinylpyrrolidone or ethanol.
[0017] Furthermore, the heat treatment is a two-stage heating treatment under an argon atmosphere, wherein the temperature of the first stage is 300-400°C and maintained for 0.5-1h, and the temperature of the second stage is increased to 600-800°C and maintained for 0.5-1h, and then washed with ethanol and deionized water after natural cooling.
[0018] The present invention also provides a method for preparing a heat dissipation coating containing modified nanoparticles, wherein the aqueous resin dispersion and the modified nanoparticles are uniformly mixed according to a ratio to obtain a mixed slurry, and then a defoamer, a dispersant, and a leveling agent are added to the mixed slurry, and the mixed slurry is ball-milled at a rotation speed of 500-1000 rpm for 1-5 hours to obtain the heat dissipation coating.
[0019] The beneficial effects of the present invention are:
[0020] The modified nanoparticles proposed in the present invention are applied to heat dissipation coatings, and the heat dissipation performance is significantly better than that of nano-alumina, and at the same time, it has good adhesion and excellent hardness, and the thermal conductivity loss of the modified nanoparticle heat dissipation coating of the present invention is extremely small after moisture absorption treatment. The modified nanoparticles proposed in the present invention have good dispersibility and are not easy to agglomerate in the coating. The interaction between the nanoparticles and the coating matrix is strong, so that the adhesion and hardness of the coating are enhanced. DETAILED DESCRIPTION
[0021] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0022] 1. Materials
[0023] Unless otherwise specified, the methods used in the present invention are conventional methods known to those skilled in the art, and the reagents and other materials used are commercially available products unless otherwise specified.
[0024] The raw materials for preparing the heat dissipation coating of the present invention include, by weight, 40-60 parts of aqueous resin dispersion, 15-20 parts of modified nanoparticles, 0.1-0.2 parts of defoaming agent, 0.1-0.5 parts of dispersant, and 1-2 parts of leveling agent;
[0025] The solid content of the aqueous resin dispersion is 30-50wt%; the aqueous resin dispersion is one or a combination of aqueous acrylic resin, aqueous epoxy resin, aqueous polyurethane, and aqueous silicone resin;
[0026] Wherein, the preparation of modified nanoparticles comprises the following steps:
[0027] (1) Ultrasonically dispersing the dried nanoparticles in 75 wt% ethanol, adding a silane coupling agent, condensing and refluxing for 1-2 h, centrifuging in a high-speed centrifuge for 5-10 min to obtain a precipitate, washing with ethanol, repeating 3-5 times, and vacuum drying for 2-4 h to obtain;
[0028] The nanoparticles are one of nanoaluminum oxide, nanoboron nitride, nanosilicon nitride or nanoaluminum nitride; and the added amount of the silane coupling agent is 2-4% of the mass of the nanoparticles.
[0029] (2) dissolving citric acid in deionized water to obtain a citric acid solution, then ultrasonically dispersing graphene powder in the citric acid solution, adjusting the pH to 7-8 with sodium hydroxide, then sealing the solution in a reactor, heating to 200-240° C., keeping the temperature constant for 12-48 hours, cooling, taking out the reactant, washing and drying, and the mass ratio of citric acid to graphene powder is (5-10):1;
[0030] (3) By mass percentage, 10-30% of the treated nanoparticles and 70-90% of the treated graphene are uniformly dispersed in a solvent, and the filtrate is placed in a reaction furnace after filtration, and subjected to a two-stage heating treatment under an argon atmosphere, wherein the temperature of the first stage is maintained at 300-400° C. for 0.5-1 h, and the temperature of the second stage is increased to 600-800° C. and maintained for 0.5-1 h. After natural cooling, the modified nanoparticles are washed with ethanol and deionized water, and dried and ground to obtain modified nanoparticles; the solvent is N-methylpyrrolidone, polyvinylpyrrolidone or ethanol.
[0031] The aqueous resin dispersion and the modified nanoparticles are uniformly mixed according to a ratio to obtain a mixed slurry, and then a defoamer, a dispersant and a leveling agent are added to the mixed slurry. The mixed slurry is ball-milled at a rotation speed of 500-1000 rpm for 1-5 hours to obtain a heat dissipation coating.
[0032] 2. Methods
[0033] 2.1 Study on the effect of modified nanoparticles on the performance of heat dissipation coatings
[0034] In this experiment, nano-alumina was selected as the nanoparticle for research.
[0035] The water-based resin dispersion of this test is water-based polyurethane, the dispersant is BYK-164 dispersant, the defoamer is EFKA-2526 defoamer, and the leveling agent is BYK-358N leveling agent.
[0036] 2.1.1 Preparation of modified nanoparticles: Dry nano-alumina was uniformly dispersed in 75wt% ethanol by ultrasonication, KH-580 silane coupling agent was added and condensed and refluxed for 2h, the amount of KH-580 silane coupling agent was 3% of the mass of nano-alumina, centrifuged in a high-speed centrifuge for 10min to obtain a precipitate, washed repeatedly with ethanol for 3 times, and vacuum dried for 2h to obtain a solid (modified nano-alumina);
[0037] Dissolve citric acid in an appropriate amount of deionized water to obtain a citric acid solution, then ultrasonically disperse graphene powder in the citric acid solution, the mass ratio of citric acid to graphene powder is 10:1, and then use sodium hydroxide to adjust the pH to 7-8, then seal the solution in a reactor, place it in a reactor and heat it to 220°C, keep the temperature constant for 48 hours, take out the reactant after cooling, wash and dry it, and obtain solid two;
[0038] By mass percentage, 20% of solid one and 80% of solid two were ultrasonically dispersed in polyvinyl pyrrolidone, the dispersion was filtered, and the filtrate was placed in a high-temperature reaction furnace and subjected to a two-stage heating treatment under an argon atmosphere. The temperature of the first stage was maintained at 350±20°C for 1h, and the temperature of the second stage was increased to 700±20°C and maintained for 1h. After natural cooling, the particles were washed with ethanol and deionized water, and dried and ground to obtain modified nanoparticles.
[0039] 2.1.2 Preparation of heat dissipation coating: According to weight, 60 parts of waterborne polyurethane and 20 parts of nano alumina (Group 1), modified nanoparticles (Group 2), ground solid one (modified nano alumina, Group 3) and ground solid two (Group 4) were mixed evenly to obtain four mixed slurries, and then 0.2 parts of defoaming agent, 0.5 parts of dispersant and 2 parts of leveling agent were added to the four mixed slurries respectively, and the mixed slurries were ball milled at 500 rpm for 2 hours to obtain four groups of heat dissipation coatings.
[0040] 2.1.3 Thermal coating performance test and conclusion
[0041] Thermal conductivity: Four groups of heat dissipation coatings were stirred evenly and then sprayed onto a substrate with release paper attached. After spraying, the substrate was cured until a uniform and stable coating was formed on the substrate. The release paper was torn off to obtain the test sample. Five samples were obtained for each group of heat dissipation coatings.
[0042] The thermal conductivity of the above samples was tested by the heat flow meter method to obtain the thermal conductivity λ1. The above samples were immersed in deionized water at 25±5°C and ultrasonically treated at 1000W for 30 minutes to simulate a liquid environment. After being fished out and naturally dried, the thermal conductivity was tested again to obtain the thermal conductivity λ2. The thermal conductivity loss was (λ1-λ2) / λ1×100%.
[0043] Adhesion: Each coating was tested according to the cross-cut test of paint and varnish film in accordance with standard GB / T 9286.
[0044] Hardness: The paint film hardness was tested according to the standard GB / T 6739 paint and varnish pencil method.
[0045] The results of the above performance tests are shown in Table 1:
[0046] Table 1 Group 1-4 coating performance test results
[0047]
[0048] It can be seen from the above test results that the modified nanoparticles proposed in the present invention are applied to the heat dissipation coating, and the heat dissipation performance is significantly better than that of nano-alumina, and its adhesion and hardness are also maintained at a high level. Group 1 also verified that after the nano-alumina heat dissipation coating was subjected to moisture absorption treatment, the thermal conductivity loss reached 15.6%. After it was modified with a silane coupling agent, the initial thermal conductivity decreased, and its adhesion and hardness also decreased, but the thermal conductivity loss was reduced to 9.6%. The thermal conductivity loss of the modified nanoparticle heat dissipation coating of the present invention after moisture absorption treatment was extremely small.
[0049] The reason may be that citric acid generates graphene quantum dots during the reaction, which enhance the interaction between the graphene quantum dots and waterborne polyurethane. Graphene quantum dots are zero-dimensional structures, which are not easy to settle compared to the two-dimensional structure of graphene. Nano-alumina, graphene quantum dots and graphene are combined with each other to form a continuous structure, which significantly enhances the heat dissipation effect of the coating, and further improves the dispersibility of thermal conductive fillers in waterborne polyurethane, so that the overall performance of the coating is improved. In addition, graphene quantum dots and graphene may have coated the modified nano-alumina, greatly reducing its thermal conductivity loss.
[0050] Another possibility is that under high-temperature sealing conditions, citric acid and graphene undergo a carbon functional reaction to generate organic molecules that react with functional groups such as hydroxyl and carboxyl on the surface of graphene. That is, citric acid performs carbon functional modification on graphene, so that when it reacts with nano-alumina at high temperature, the nano-alumina adheres tightly to the surface of graphene, which can effectively prevent graphene from agglomerating and enhance the bonding with water-based polyurethane, thereby improving the overall performance of the coating.
[0051] Based on the above experiments, this study further proposed that graphene powder and graphene quantum dots are mixed in a mass ratio of 10:1, and then 80% of the mass ratio of the mixture is mixed with 20% of solid (modified nano-alumina) as an additive. 60 parts of waterborne polyurethane and 20 parts of additives are mixed evenly to obtain a mixed slurry, and then 0.2 parts of defoamer, 0.5 parts of dispersant, and 2 parts of leveling agent are added to the mixed slurry respectively, and the mixed slurry is ball-milled at a speed of 500rpm for 2h to obtain a heat dissipation coating.
[0052] The above heat dissipation coating was tested using method 2.1.3, and the thermal conductivity λ1 was 9.7W / (m·K), the thermal conductivity λ2 was 8.4W / (m·K), the thermal conductivity loss rate was 13.4%, the adhesion was level 1, and the hardness was 5H. The above test results show that the addition of graphene quantum dots alone cannot significantly improve the thermal conductivity loss and the overall performance of the coating.
[0053] 2.1.4 Extension
[0054] Further improvements were made to the preparation of modified nanoparticles in 2.1.1:
[0055] Dissolve citric acid in an appropriate amount of deionized water to obtain a citric acid solution, then ultrasonically disperse graphene powder in the citric acid solution, the mass ratio of citric acid to graphene powder is 10:1, then add triethylenediamine, the addition amount of triethylenediamine is 50% of the mass of the graphene powder, and after mixing, use sodium hydroxide to adjust the pH to 7-8. Triethylenediamine is weakly alkaline and can reduce the amount of sodium hydroxide. Then seal the solution in a reactor, place it in a reactor, heat it to 220°C, keep the temperature constant for 48 hours, take out the reactant after cooling, wash and dry it, and obtain solid two;
[0056] According to 2.1.2, grind the solid phase II and mix it evenly with the waterborne polyurethane. Then add the defoamer, dispersant and leveling agent into the mixed slurry respectively. Ball mill the mixed slurry at 500 rpm for 2 h to obtain the heat dissipation coating.
[0057] The above heat dissipation coating was tested using method 2.1.3, and the thermal conductivity λ1 was 11.4 W / (m·K), the thermal conductivity λ2 was 11.1 W / (m·K), the adhesion was level 0, and the hardness was 6H.
[0058] This extension further enhances the heat dissipation performance of the coating by further strengthening the modification of triethylenediamine on the basis of citric acid-modified graphene. It is speculated that the reason is that triethylenediamine has catalytic and cross-linking effects, which increases the interaction and bonding strength of graphene with water-based polyurethane. In addition, it was found that the curing speed was significantly accelerated when making samples, which laid a good foundation for the development of quick-drying heat dissipation coatings.
[0059] 2.2 Study the effect of different modified nanoparticles on the performance of heat dissipation coatings
[0060] Based on 2.1.1, the effects of nano-alumina, nano-boron nitride, nano-silicon nitride and nano-aluminum nitride on the performance of heat dissipation coatings are studied.
[0061] Dry nano-boron nitride, nano-silicon nitride and nano-aluminum nitride were ultrasonically uniformly dispersed in 75wt% ethanol respectively, and KH-580 silane coupling agent was added for condensation and reflux for 2 hours. The amount of KH-580 silane coupling agent was 3% of the mass of the nanoparticles. The precipitate was obtained by centrifugation in a high-speed centrifuge for 10 minutes, and the precipitate was repeatedly washed with ethanol for 3 times and vacuum dried for 2 hours to obtain particles one, two and three.
[0062] According to the mass percentage, 20% of particle one, particle two and particle three and 80% of solid two were ultrasonically dispersed in polyvinyl pyrrolidone, the dispersion was filtered, and the filtrate was placed in a high-temperature reactor and subjected to a two-stage heating treatment under an argon atmosphere. The temperature of the first stage was maintained at 350±20°C for 1h, and the temperature of the second stage was increased to 700±20°C and maintained for 1h. After natural cooling, the particles were washed with ethanol and deionized water, and dried and ground to obtain modified nanoparticles one (group 5), modified nanoparticles two (group 6), and modified nanoparticles three (group 7).
[0063] According to 2.1.2, the modified nanoparticles 1 (group 5), modified nanoparticles 2 (group 6), and modified nanoparticles 3 (group 7) were ground and evenly mixed with waterborne polyurethane, and then the defoamer, dispersant, and leveling agent were respectively added to the mixed slurry, and the mixed slurry was ball-milled at 500 rpm for 2 h to obtain three groups of heat dissipation coatings.
[0064] The above heat dissipation coating was tested using method 2.1.3. The results of the performance test are shown in Table 2:
[0065] Table 2 Group 5-7 coating performance test results
[0066]
[0067] It can be seen from the above test results that nano-aluminum oxide, nano-boron nitride, nano-silicon nitride and nano-aluminum nitride have almost no effect on the adhesion of heat dissipation coatings. Although the thermal conductivity of nano-aluminum oxide (30-70W / (m·K)) is less than the thermal conductivity of nano-boron nitride (50-100W / (m·K)), nano-silicon nitride (54-105W / (m·K)) and nano-aluminum nitride (60-200W / (m·K)), when applied to coatings, the thermal conductivity of nano-aluminum oxide is higher than that of nano-boron nitride and nano-silicon nitride. It is speculated that aluminum ions, as metal ions, have a complexing effect with graphene or graphene quantum dots, or that graphene can accelerate the transfer speed of aluminum ions. Among them, nano-boron nitride and nano-silicon nitride themselves do not absorb moisture, so the thermal conductivity loss rate is naturally reduced. Since nano-boron nitride, nano-silicon nitride and nano-aluminum nitride have high hardness, they have good dispersibility in water-based polyurethane after being treated by the present invention, so that their hardness is further increased.
[0068] 2.3 Study the effects of different aqueous dispersions on the performance of heat dissipation coatings
[0069] Based on 2.1.1, the effects of water-based acrylic resin, water-based epoxy resin, water-based polyurethane and water-based silicone resin on the performance of heat dissipation coatings were studied.
[0070] According to 2.1.2, the modified nanoparticles were mixed evenly with water-based acrylic resin, water-based epoxy resin and water-based silicone resin respectively, and then the defoamer, dispersant and leveling agent were added to the mixed slurry respectively. The mixed slurry was ball-milled at 500 rpm for 2 h to obtain three groups of heat dissipation coatings.
[0071] The above heat dissipation coating was tested using method 2.1.3. The results of the performance test are shown in Table 3:
[0072] Table 3 Coating performance test results of different aqueous dispersions
[0073]
[0074] It can be seen from the above test results that the modified nanoparticles proposed by the present invention can be applied to a variety of water-based coatings, and while having a significant heat dissipation effect, its adhesion and hardness are also maintained at a high level. The above-mentioned embodiments only express several implementation methods of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present invention, several modifications and improvements can also be made, which all belong to the protection scope of the present invention.
Claims
1. A heat dissipation coating containing modified nanoparticles, characterized in that: The raw materials for preparing the heat dissipation coating include, by weight, 40-60 parts of aqueous resin dispersion, 15-20 parts of modified nanoparticles, 0.1-0.2 parts of defoaming agent, 0.1-0.5 parts of dispersant, and 1-2 parts of leveling agent; The modified nanoparticles are obtained by modifying nanoparticles with a silane coupling agent, mixing with graphene, and then heat treating the nanoparticles. The nanoparticles are one of nano-aluminum oxide, nano-boron nitride, nano-silicon nitride, or nano-aluminum nitride.
2. The heat dissipation coating containing modified nanoparticles according to claim 1, characterized in that: The solid content of the aqueous resin dispersion is 30-50wt%; the aqueous resin dispersion is one or a combination of aqueous acrylic resin, aqueous epoxy resin, aqueous polyurethane, and aqueous silicone resin.
3. The heat dissipation coating containing modified nanoparticles according to claim 1, characterized in that: The preparation of the modified nanoparticles comprises the following steps: (1) uniformly dispersing the dried nanoparticles in 75 wt% ethanol, adding a silane coupling agent to condense and reflux, centrifuging to obtain a precipitate, washing, and vacuum drying; mixing the graphene powder with a citric acid solution, adjusting the pH to alkaline, and sealing the mixture in a container, heating the mixture to react at a constant temperature, cooling the mixture to room temperature after the reaction is completed, and taking out the reactant, washing, and drying the mixture; (2) uniformly dispersing the treated nanoparticles and the treated graphene in a solvent, filtering the filtrate, heat-treating the filtrate, and grinding to obtain modified nanoparticles.
4. The heat dissipation coating containing modified nanoparticles according to claim 3, characterized in that: The added amount of the silane coupling agent is 2-4% of the mass of the nanoparticles.
5. The heat dissipation coating containing modified nanoparticles according to claim 3, characterized in that: The processing process of the graphene powder is specifically as follows: dissolving citric acid in deionized water to obtain a citric acid solution, then dispersing the graphene powder in the citric acid solution, adjusting the pH to 7-8 with sodium hydroxide, and then sealing the solution in a reactor, heating it to 200-240° C., keeping the temperature constant for 12-48 hours, taking out the reactant after cooling, washing and drying, and the mass ratio of citric acid to graphene powder is (5-10):
1.
6. The heat dissipation coating containing modified nanoparticles according to claim 5, characterized in that: After dispersing the graphene powder in the citric acid solution, triethylenediamine is added, mixed, and then the pH is adjusted to 7-8 using sodium hydroxide. The amount of triethylenediamine added is 50% of the mass of the graphene powder.
7. The heat dissipation coating containing modified nanoparticles according to claim 3, characterized in that: In terms of mass percentage, the treated nanoparticles account for 10-30%, and the treated graphene accounts for 70-90%.
8. The heat dissipation coating containing modified nanoparticles according to claim 7, characterized in that: The solvent is N-methylpyrrolidone, polyvinylpyrrolidone or ethanol.
9. The heat dissipation coating containing modified nanoparticles according to claim 7, characterized in that: The heat treatment is a two-stage heating treatment under an argon atmosphere. The temperature of the first stage is 300-400° C. and maintained for 0.5-1 h. The temperature of the second stage is increased to 600-800° C. and maintained for 0.5-1 h. After natural cooling, the product is washed with ethanol and deionized water.
10. A method for preparing the heat dissipation coating containing modified nanoparticles according to claims 1-9, characterized in that: The aqueous resin dispersion and the modified nanoparticles are uniformly mixed according to a ratio to obtain a mixed slurry, and then a defoamer, a dispersant, and a leveling agent are added to the mixed slurry. The mixed slurry is ball-milled at a rotation speed of 500-1000 rpm for 1-5 hours to obtain a heat dissipation coating.
Citation Information
Cited By
Multifunctional coating based on acrylic resin and production process thereof
CN120484589A